PARENTAL SUPPORT FOR ADOLESCENTS WITH BIPOLAR DISORDER SYMPTOMS USING COGNITIVE BEHAVIORAL THERAPHY - Ilham Yunus Simbolon (Psikoislamedia : Jurnal Psikologi, 2024)
Adolescents in their development experience symptoms of bipolar disorder that hinder adolescent development. This study presents a critical analysis of previous research findings in the context of developing intervention strategies for adolescents with bipolar disorder symptoms. We evaluated the effectiveness of cognitive-behavioral therapy applied to a group of adolescents with active parental support. This study utilized qualitative-descriptive methods to elucidate the positive impact of the therapy in improving psychological well-being and management of bipolar symptoms. Although the findings indicated the success of the therapy, the limitations of previous research became a focal point for this follow-up study. The results showed that parents' presence and participation played an important role in designing and reinforcing the therapy intervention. Emotional and educative support from parents provides a solid foundation to accelerate the adolescent's healing process. These findings provide insight into the importance of integrating family support in designing effective cognitive-behavioral therapy strategies to manage bipolar disorder symptoms in adolescents.